2007
DOI: 10.1152/ajpgi.00524.2006
|View full text |Cite
|
Sign up to set email alerts
|

Clotrimazole-sensitive K+ currents regulate pacemaker activity in interstitial cells of Cajal

Abstract: Interstitial cells of Cajal (ICC) are pacemaker cells for gut peristaltic motor activity. Compared with cardiac pacemaker cells, little is known about mechanisms that regulate ICC excitability. The objective of the present study was to investigate a potential role for clotrimazole (CTL)-sensitive K currents (I(CTL)) in the regulation of ICC excitability and pacemaker activity. ICC were studied in situ and in short-term culture by using the whole cell patch-clamp configuration. In situ, ICC exhibited spontaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…We found that the background current was carried by potassium and was of the "transient outward" type as characterized in cardiac cells (7). This furthers our previous study that was the first to record single potassium channels in ICC (36).…”
supporting
confidence: 83%
“…We found that the background current was carried by potassium and was of the "transient outward" type as characterized in cardiac cells (7). This furthers our previous study that was the first to record single potassium channels in ICC (36).…”
supporting
confidence: 83%
“…Activation of I K channels in enterocytes stimulates fluid secretion [44], and this could have an indirect effect on segmentation. Further, clotrimazole-sensitive potassium currents have been seen in ICC in mice [45]. Even though there is little slow-wave activity in the guinea-pig, if the I K channels blockers were acting on ICCs, they would be expected to influence the properties of isolated bursts, rather than the contractile episodes, because of the time course of potassium currents in these cells [46].…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies are required to identify the ion channels involved, specifically K + channels that may be involved in the GSS-induced pacemaker potential depolarizations. There are many K + channels that possibly regulate ICC or GI motility, such as voltage-dependent K + channels (Kv channels) [42], Na + -K + -Cl – cotransporters [43], ATP-sensitive K + channels [44], voltage-gated Kv11.1 (hERG) channels [45], K V 7.5 channels [46], transient outward K + channels [47], Ca 2+ -activated K + channels [48], E-4031-sensitive K + channels [49], 4-AP-sensitive K + channels [50], and clotrimazole-sensitive K + channels [51]. GSS may have an effect on K + channels in ICCs and the possible effect of this on the pacemaker potential depolarization requires investigation.…”
Section: Discussionmentioning
confidence: 99%